Udvidende fortolkning eller analogi – straffelovens § 1 - Bo Langsted, Lars (Nordisk Tidsskrift for Kriminalvidenskab, 2022)
The article contains a clarification of the difference between »expanded interpretation« and »analogy« in criminal law. Doubt about the terms is raised by newer Danish literature stating that expanded interpretation is similar to analogy. In the article it is argued that a large difference exists between the two terms and that it is a slippery road in the context of legal rights to let analogy be included in the term expanded interpretation.